2017
DOI: 10.1111/1751-7915.12833
|View full text |Cite
|
Sign up to set email alerts
|

Architects of nature: growing buildings with bacterial biofilms

Abstract: SummaryIn his text ‘On Architecture’, Vitruvius suggested that architecture is an imitation of nature. Here we discuss what happens when we begin using nature in architecture. We describe recent developments in the study of biofilm structure, and propose combining modern architecture and synthetic microbiology to develop sustainable construction approaches. Recently, Kolodkin‐Gal laboratory and others revealed a role for precipitation of calcium carbonate in the maturation and assembly of bacterial communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
8
0
2
Order By: Relevance
“…An earlier report showed that minerals structurally support the morphogenesis of bacterial colonies in the Gram-positive bacterium Bacillus subtilis [9] and in Mycobacterium species [8,9]. Biogenic minerals also provide structural integrity to biofilm matrix and act as a scaffold to protect bacterial cells from shear forces and antimicrobial agents [10]. An earlier report demonstrated the presence of CaCO 3 in the matrix of B. subtilis and Mycobacterium smegmatis biofilms, and implied the association of matrix mineral with other bacterial species [9].…”
Section: Highlightsmentioning
confidence: 99%
“…An earlier report showed that minerals structurally support the morphogenesis of bacterial colonies in the Gram-positive bacterium Bacillus subtilis [9] and in Mycobacterium species [8,9]. Biogenic minerals also provide structural integrity to biofilm matrix and act as a scaffold to protect bacterial cells from shear forces and antimicrobial agents [10]. An earlier report demonstrated the presence of CaCO 3 in the matrix of B. subtilis and Mycobacterium smegmatis biofilms, and implied the association of matrix mineral with other bacterial species [9].…”
Section: Highlightsmentioning
confidence: 99%
“…However, development of building systems or cleaning products which intentionally create biofilms have also been utilized to positive effect. Recently, microbial biofilms have been used to reinforce building surfaces instead of decomposing them; namely, through mineralization and deposition of calcium carbonate into concrete [129]. The hydrophobic nature of many bacterial biofilms can impart that protective hydrophobicity onto building surfaces [130], as well.…”
Section: Moisture and Relative Humiditymentioning
confidence: 99%
“… 3 , 6 , 7 Recently, we and others showed that precipitation of calcium carbonate contributes to the assembly of the complex biofilm architecture. 8 13 While calcium is available from the environment, bicarbonate is actively produced by CO 2 hydration (CO 2 + H 2 O ↔ HCO 3 + H + ), where the source of CO 2 can be a byproduct of bacterial metabolism or of the immediate environment. 14 16 In clinic, precipitation of calcium carbonate was shown to promote catheter colonization, active infection and interspecies interactions.…”
Section: Introductionmentioning
confidence: 99%